Cerebral infarction in advanced non-small cell lung cancer: a case control study. Issue 1 (December 2016) - Kato, Motoyasu; Shukuya, Takehito; Mori, Keita; Kanemaru, Ryota; Honma, Yuichiro; Nanjo, Yuta; Muraki, Keiko; Shibayama, Rina; Koyama, Ryo; Shimada, Naoko; Takahashi, Fumiyuki; Takahashi, Kazuhisa
Abstract Background Advanced non-small cell lung cancer (NSCLC) patients often develop thromboembolic events, including cerebral infarction (CI). However, the relationship between advanced NSCLC and CI has not been thoroughly investigated. We examined the association between advanced NSCLC and CI and risk factors for CI in advanced or post-operative recurrent NSCLC patients. Methods We retrospectively investigated 515 patients diagnosed with advanced or post-operative recurrent NSCLC at Juntendo University Hospital between April 2009 and March 2014. Results Among the 515 patients evaluated, 15 patients (2.9 %) developed CI after diagnosis of advanced or post-operative recurrent NSCLC. Univariate and multivariate analyses were conducted, and brain metastasis was the only significant independent risk factor for CI (odds ratio 5.24, 95 % confidence interval 1.72–16.10, p  = 0.004). The incidence was 6.3 % in these patients. The median survival time was 36 days, and 1-year survival rate was 6.7 % after development of CI. Overall survival from diagnosis of advanced NSCLC or post-operative recurrence was significantly shorter in patients with CI than in patients without CI (223 days versus 895 days; HR, 3.46; 95 % confidence interval, 2.04–6.02;p  = 0.001). Conclusions The incidence of CI is high in advanced or post-operative recurrent NSCLC, and is especially higher in patients with brain metastasis than in those without brain metastasis. Moreover, CI may affect patient's prognosis. Careful monitoring for the development of CI in patients with advanced or post-operative recurrent NSCLC is needed, especially for patients with brain metastasis.